A Blockchain Decentralized Public Key Infrastructure Model - Konoplev, A. S.; Busygin, A. G.; Zegzhda, D. P. (Automatic control and computer sciences, 2018)
— This article presents a comparative analysis of available solutions in authenticating access subjects in computer-aided information and telecommunication systems. Centralized and decentralized public key infrastructures (PKIs) are considered, and their weaknesses are brought to light. A blockchain model of decentralized PKI for access subject authentication in computer-aided information and telecommunication systems is proposed. The current embodiments of blockchain PKIs are checked for compliance with the proposed model.